Eosinophilic Esophagitis: real-life outcomes over 10 years in a Canadian pediatric centre - Deretic, Nikola; Bush, Jonathan W.; Erdle, Stephanie C.; Chan, Edmond S.; Avinashi, Vishal (Frontiers in Pediatrics, 2025)
ObjectiveDespite Eosinophilic Esophagitis (EoE) being a chronic condition, many studies focus on the short-term. This study characterizes patients, treatment effectiveness and outcomes in a pre-biologic era.MethodsThis cohort study (2012–2022) at British Columbia (BC) Children's Hospital in Vancouver, Canada analyzed data from the EoE Registry which was hosted on Research Electronic Data Capture (REDCap) for participating patients <18 years with biopsy-proven diagnosis (≥15 eosinophils/hpf) including demographics, symptoms, allergic history, medications, endoscopy and histology.Results247 patients (71.2% White, 16.7% South Asian, 78.1% male, median age 9 years) were followed over a median 3-year follow up. 85.2% had at least one atopic condition and 17.4% reported Cow's Milk Protein Allergy in infancy. 19.0% lacked follow up endoscopy and in clinic follow-up, 18.2% were on no therapy. At last endoscopy of those on treatment (n = 200), 39.0% used swallowed topical corticosteroids (50.0% remission), 23.0% proton pump inhibitors (29.0% remission), and 39.0% elimination diets (34.0% remission). Over half on medications had imperfect adherence. Overall, 39.0% achieved remission (<15 eosinophils/hpf), (mean peak eosinophils decreased from 55 to 27/hpf, strictures from 7.5% to 2.7%).ConclusionsThis Canadian study reveals remission rates lower than short term studies, but a reduction in strictures in follow-up. Real-life challenges, such as not returning for follow up endoscopy (∼20%), despite no direct care costs, challenges with adherence with ∼20% not taking any therapy and over half not taking medications as prescribed contribute towards remission rates below 50% regardless of treatment. Better patient engagement, addressing barriers to treatment and follow up and exploring novel therapies are needed.